Optimizing process of check-in and security check at airport terminal - Široký, Jaromír; Hlavsová, Pavlína (EDP Sciences, 2018)
The paper deals with possibilities of optimizing the process of check-in and security check at airport terminals using simulation program. Proposed model is based on real parameters and simulated in the environment of the program Tecnomatix Plant Simulation. This program simulates the process of check-in and security check. Queuing theory will be used for simulation. Principally it means queuing customers, i.e. accumulation of requests, in front of a service centre. Limiting criteria for optimization include operating conditions of airport terminals, financial means connected with personnel resources, legal standards related to safety in air transport and level of service indicators. The aim of the paper is to create a model, which analyses the passenger flow processes at the airport terminal and could be used for evaluating potential changes of the check-in and security check system at airport terminals.
Optimalizace procesu odbavení a bezpečnostní kontroly v letištním terminálu
Keywords: Optimizing proces; check-in; security check; airport terminal.; optimalizace; odbavení cestujících; bezpečnostní kontrola; letecký terminál.